TEACHING SPEAKING SKILLS THROUGH CONVERSATION PRACTICE DUET WITH ME VIDEO FOR STUDENTS’ ENGLISH EDUCATION STUDY PROGRAM AT IAIN PALOPO - Nurul Mifta; Sultan Baa (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The objectives of this study were to discover the effectiveness of Conversation Practice Duet with Me Video in improving students’ speaking skill in English Education Study Program at IAIN Palopo and discover the students’ perceptions of the implementation of Conversation Practice Duet with Me Video in speaking class at the first semester of English Education Study Program at IAIN Palopo. This study applied quasi experimental design. The population in this study was the first semester of English Education Study Program at IAIN Palopo Academic Years 2023/2024 that consisted of two classes. Class B consisted of 16 students as an experimental class and class A consisted of 16 students as a control class. There were two instruments in this study, speaking test and questionnaire. The data of this study were collected by speaking test in the pretest and posttest of two classes which analyzed by using SPSS 27. Based on the analysis of the statistics showed that the independent sample test which sig. value was smaller than t-table 0.001<0.05 from the degree of freedom 30. The result showed that null hypothesis (H0) was rejected and alternative hypothesis (H1) was accepted. It could be concluded that the use of conversation practice duet with me video was effective to be implemented in improving students’ speaking skill in term of accuracy, fluency, and comprehensibility. Besides, the questionnaire was given to the experimental class after having posttest and the result of the questionnaire showed that most of the students were interest toward the implementation of using conversation practice duet with me video in teaching and learning speaking